Challenges of teacher education in a context of educational reform: an analysis from the scottish reform paradigm “Curriculum for Excellence” (Revista Contexto & Educação, 2024)
This article aims to investigate the challenges involved in the initial and continuing training of teachers for Basic Education in Brazil in the context of the educational reform recently implemented in the country through the BNCC, using as paradigm the process of educational reform occurred in Scotland, which culminated in the implementation of the “Curriculum for Excellence” in that country. The research is qualitative in nature, and the investigation consisted of an in-depth analysis of the documents on which the Scottish and Brazilian proposals were based. The data presented are 12 articles that were written from a research project, related to the “challenges of teacher education in a context of educational reform” and that will be analysed here from the paradigm of the successful process of educational reform that occurred in Scotland. Based on the parallels we identified between the Scottish and Brazilian curriculum reform processes, our results allow us to contribute to the deepening of the ongoing discussions in Brazil about the BNCC and the reform of secondary education, as well as with the eventual reflections on needs for course corrections in the reform process in Brazil.
Keywords: teacher education; educational reform; curriculum for excellence; BNCC